The roles of phospholipase C-β related signals in the proliferation, metastasis and angiogenesis of malignant tumors, and the corresponding protective measures - Wu, Yu-Nuo; Su, Xing; Wang, Xue-Qin; Liu, Na-Na; Xu, Zhou-Wei (Frontiers in Oncology, 2023)
PLC-β is widely distributed in eukaryotic cells and is the key enzyme in phosphatidylinositol signal transduction pathway. The cellular functions regulated by its four subtypes (PLC-β1, PLC-β2, PLC-β3, PLC-β4) play an important role in maintaining homeostasis of organism. PLC-β and its related signals can promote or inhibit the occurrence and development of cancer by affecting the growth, differentiation and metastasis of cells, while targeted intervention of PLC-β1-PI3K-AKT, PLC-β2/CD133, CXCR2-NHERF1-PLC-β3, Gαq-PLC-β4-PKC-MAPK and so on can provide new strategies for the precise prevention and treatment of malignant tumors. This paper reviews the mechanism of PLC-β in various tumor cells from four aspects: proliferation and differentiation, invasion and metastasis, angiogenesis and protective measures.